Niobic acid nanoparticle catalysts for the aqueous phase transformation of glucose and fructose to 5-hydroxymethylfurfural. Issue 19 (18th August 2016) - Reche, Mariano Tapia; Osatiashtiani, Amin; Durndell, Lee J.; Isaacs, Mark A.; Silva, Ângela; Lee, Adam F.; Wilson, Karen
Abstract : The first catalytic application of a nanoparticulate niobia solid acid prepared from a high area peroxo niobic acid sol, and its SBA-15 supported analogue, is demonstrated for the heterogeneously catalysed aqueous phase conversion of glucose and fructose to 5-HMF. Abstract : A family of bulk and SBA-15 supported peroxo niobic acid sols were prepared by peptisation of niobic acid precipitates with H2 O2 as heterogeneous catalysts for aqueous phase glucose and fructose conversion to 5-hydroxymethylfurfural (5-HMF). Niobic acid nanoparticles possess a high density of Brønsted and Lewis acid sites, conferring good activity towards glucose and fructose conversion, albeit with modest 5-HMF yields under mild reaction conditions (100 °C). Thermally-induced niobia crystallisation suppresses solid acidity and activity. Nanoparticulate niobic acid dispersed over SBA-15 exhibits pure Brønsted acidity and an enhanced Turnover Frequency for fructose dehydration.